Prevalence of HIV-1 Subtypes and Antiretroviral Drug Resistance Mutations in Nepal - Bhusal, Nirajan; Sutthent, Ruengpung; Horthongkham, Navin; Athipanyasilp, Niracha; Kantakamalakul, Wannee (Current HIV Research, 2016)
Background: There have been very few reports of HIV-1 subtypes and drug resistance mutations (DRMs) from Nepal which is geographically located between two high-prevalence HIV-1 infection countries, China and India. Objective: The aim of this study was to determine prevalence of acquired and transmitted DRMs and HIV-1 subtypes in Nepal. Methods: Thirty-five HIV-1 seropositive samples from central region of Nepal were collected in 2011. The subjects were divided into two groups, antiretroviral (ARV) drug naïve group (n=15) and antiretroviral treatment (ART) group (n=20), 90% (18/20) of them received zidovudine, lamivudine and nevirapine (AZT/3TC/NVP) regimen. HIV pol (protease and reverse transcriptase regions) nucleotide sequences were analyzed by Viroseq HIV-1 Genotyping System. Nearly full-length genomic (NFLG) sequences of 10 samples were performed. Results: NFLG genotyping revealed that 80% of samples were infected with subtype C and 20% with recombinants (C/D/H and C/A). Phylogenetic analysis of 35 pol sequences from Nepal were subtype C. The prevalence of acquired DRMs to NNRTIs and NRTIs was 15% (3/20). DRMs to NVP, K103N and V179D, and to NRTIs were observed at 11.1% (2/18) and 5% (1/20), respectively. The prevalence of DRMs to rilpivirine for E138A/G was 5.7%. The minor protease inhibitors (PI) associated mutations (A71T/V and T74S) were observed in 5/35 (14.3%) subjects. Conclusion: This is the first report of NFLG HIV-1 genomic sequences and DRMs from Nepal. National surveillance of HIV DRMs to ARVs and molecular epidemiology study should be done annually for better prevention and treatment of HIV infection in Nepal.
Keywords: Nepal